An Analysis of Students’ Ability in Writing A Greeting Card At MTS Simpang Dolok Batu Bara - Nurlaili, Diana, (Pusdikra-Publishing.com, 2023)
The purpose of this research was to investigate the students’ ability in writing a greeting card at MTs Simpang Dolok Batubara.This observation was taken 6 days which started from Monday, 11th December 2023 to Saturday, the 16th of December 2023. The Qualitative Research Method was used in this research. The subjects of this research chosen randomly were 7 students as the representative of students in the eight grades of Junior High School Students of MTs Simpang Dolok Batubara, academic year 2023-2024. The populations from this research were the whole students of VIII grade of MTs Simpang Dolok Batubara. Technique of collecting data used was the observation in which the students were observed during the writing class by using observation sheet designed with theory of Brown in Moh. (2019 ) to know the ability that have been achieved by the students and all the data found from 7 subjects of research that have been analyzed by the researcher there were 4 indicators/elements, namely content, vocabulary, grammar and mechanics. After the research conducted, it was found that there were 3 students with the good level in writing skill, 3 students with the fair in writing skill, and only one students categories as the unsatisfied or poor in writi skill.. Shortly, this finding of the research was appropriate with the assumption in this research that is a greeting card is effective to increase the students’ effectivity and creativity in writing.